(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article shows the importance of the concept of time in sociolinguistics and the use of language opportunities, as well as how society members perceive this process with the help of examples. theoretical and practical illuminated. Also, a component analysis was conducted summarizing the opinions and considerations about the characteristics of time as a sociolinguistic category.